A Critique of the Book Understanding Social Science from the Perspective of Actor-Network Theory - Rahman Sharifzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Roger Trigg’s Understanding Social Science does a good job of criticizing positivist and deterministic approaches to social science, either biological, social, or psychological. In the context of critical realism, Trigg criticizes in a good and detailed way many of the common dichotomies, amongst which naive realism / non-realism is most important. Although Trigg attempts to go away from positivistic and non-critical methodologies, and in result opens up a way for rational evaluation and judgment, as we shall see, he does not develop his methodology very well; moreover, his understanding of what society is and what social structures and realities are made of may endanger the empirical aspect of his methodology. Furthermore, it seems to me that some of Trigg’s arguments in the field of rationality are ambiguous and do not go far enough in the critique of constructivists’ and relativists’ attitudes.